2017
DOI: 10.1126/science.aan3456
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular reorganization of neural circuits in the human lineage

Abstract: To better understand the molecular and cellular differences in brain organization between human and non-human primates, we performed transcriptome sequencing of sixteen regions of adult human, chimpanzee, and macaque brains. Integration with human single-cell transcriptomic data revealed global, regional, and cell-type specific species expression differences in genes representing distinct functional categories. We validated and further characterized the human specificity of genes enriched in distinct cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
202
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(223 citation statements)
references
References 71 publications
21
202
0
Order By: Relevance
“…1H). Overall, in agreement with previous works [Sousa et al, 2017a;Xu et al, 2018], more differences mapped to the human lineage (the average n=712) than to the chimpanzee (n=641) or bonobo (n=640) lineages.…”
Section: Regional Analysis Of the Human-specific Gene Expression Diffsupporting
confidence: 92%
See 1 more Smart Citation
“…1H). Overall, in agreement with previous works [Sousa et al, 2017a;Xu et al, 2018], more differences mapped to the human lineage (the average n=712) than to the chimpanzee (n=641) or bonobo (n=640) lineages.…”
Section: Regional Analysis Of the Human-specific Gene Expression Diffsupporting
confidence: 92%
“…First, we compared gene expression levels that were obtained in our study with a previously published dataset containing 16 brain regions in human and non-human primates [Sousa et al, 2017a]. We employed the same read mapping and counting procedures as described above for RNA-seq reads from the National Center for Biotechnology Information BioProjects database, accession number PRJNA236446 [Sousa et al, 2017a]. The resulting TPM values were log2 transformed, and then quantile normalization was applied.…”
Section: Expression Differences Between Speciesmentioning
confidence: 99%
“…Sousa et al. () have reported that a type of dopaminergic interneuron exclusively exists in the human neocortex. These studies could be evidence supporting the possibility that changes in monoaminergic circuits have driven the evolution of both the brain and human behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Raghanti et al (2018) demonstrated that the human striatum, a region of the brain modulating social behavior, exhibits unique neurochemical profile compared to other primates. Sousa et al (2017) have reported that a type of dopaminergic interneuron exclusively exists in the human neocortex. These studies could be evidence supporting the possibility that changes in monoaminergic circuits have driven the evolution of both the brain and human behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our parietal cortex and visuospatial functions can play a major role in the management of such interactions between the nervous system, the body interface, and technological resources [Bruner and Iriki, 2016]. Interestingly, a comprehensive analysis on neural circuits in primates evidenced major human changes in the genetic expression associated with the striatum, an element of the basal ganglia deeply involved in body management [Sousa et al, 2017].…”
Section: Visuospatial Integration and Body Cognitionmentioning
confidence: 99%